DESAGUAMENTO NATURAL DE LODOS DE UASB UTILIZANDO MANTAS GEOTEXTEIS - Vasconcellos, Atila Pavan (2022)
Dewatering is a fundamental step in the management of sludge from Waste Water Treatment Plants (WWTP), since it’s responsible for the significative reduction of volume and consequent weight, decreasing costs relative to transport and final disposal of this kind of waste. In this way, this study aims to evaluate the natural dewatering on sludges from a Upflow Anaerobic Sludge Blanket (UASB) reactor, using geotextile materials on drainage systems with different configurations, without chemical conditionings. In this research, initially, sludges from the regions of the bed and the blanket of the UASB reactor, treating municipal sewage, were characterized about their physicochemical properties, their distribution of water fractions, their dewaterability indexes and their rheological behaviour. Later, dewatering tests were realized, being divided in three steps and using three configurations. The first aimed to analyze the influence of the geotextile material used as filter on dewatering process. The second, the comparison of two of the devices used and the third, the assessment of the performance between the integration of the previous systems. Performance indexes were used to evaluate two principal aspects: reduction of free water and the retention of solids, related to the quality of the filtrate. Dewatering tests showed reduction of volume in order of 70% and the sludge cake formed above the geotextile in order of 15% of Total Solids. There was no significant difference in the results about the influence of the geotextile blankets BIDIM RT-21, RT-26 e RT-31 and the Vertical Static Dewaterer (DEV) exhibited the best results among the configurations used in the dewatering devices. The formation of a filter cake above the geotextile was noticed and it is related to the Solid Application Rates (RAS), being capable to influence in a different way the two main aspects evaluated: reduction of volume and the solids capture.